Does return migration influence fertility at home? - Simone Bertoli (IZA World of Labor, 2015)
Demographic factors in migrant-sending countries can influence international migration flows. But when migrants move across borders, they can also influence the pace of demographic transition in their countries of origin. This is because migrants, who predominantly move on a temporary basis, encounter new fertility norms in their host countries and then bring them back home. These new fertility norms can be higher or lower than those in their country of origin. So the new fertility norms that result from migration flows can either accelerate or slow down a demographic transition in migrant-sending countries.
Keywords: F22; K37; J61; 330; temporary migration; return migration; transfer of norms; fertility